2007
DOI: 10.1007/s00276-007-0233-1
|View full text |Cite
|
Sign up to set email alerts
|

Normal vascular and biliary hepatic anatomy: 3D demonstration by multidetector CT

Abstract: Due to constant innovations in radiological and surgical techniques, more accurate results are expected in the diagnostic and therapeutic procedures related to hepatic pathology. The aim of this work was to demonstrate the normal hepatic vascular and biliary anatomy using cadaveric livers and CT scans of the affected livers. Furthermore, using the CT scans, the authors intended to illustrate the most common morphological variations of the vascular and biliary anatomy. Four human cadaveric livers were injected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 13 publications
0
7
0
3
Order By: Relevance
“…Contiguous pathological and adjacent tissues were observed for location diagnosis and qualitative diagnosis. Through three-phase enhancement scanning, we were able to confirm the enhanced features of pathological changes, including benignity or malignancy, violation degree, lymph node metastasis, intrahepatic metastasis, vascular embedding and ascites, which may indicate the feasibility of tumor staging and surgical resection (1122). Through portal vein phase MPR of porta hepatis cholangiocellular carcinoma, we were able to observe that the enhanced portal vein served as a foil to the irregular shape of the porta hepatis soft tissue which blocked the common hepatic duct, invaded left and right hepatic bile ducts and caused the intrahepatic bile ducts of the right and left lobes of the liver to expand (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…Contiguous pathological and adjacent tissues were observed for location diagnosis and qualitative diagnosis. Through three-phase enhancement scanning, we were able to confirm the enhanced features of pathological changes, including benignity or malignancy, violation degree, lymph node metastasis, intrahepatic metastasis, vascular embedding and ascites, which may indicate the feasibility of tumor staging and surgical resection (1122). Through portal vein phase MPR of porta hepatis cholangiocellular carcinoma, we were able to observe that the enhanced portal vein served as a foil to the irregular shape of the porta hepatis soft tissue which blocked the common hepatic duct, invaded left and right hepatic bile ducts and caused the intrahepatic bile ducts of the right and left lobes of the liver to expand (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…For the blood supply of the extrahepatic bile ducts, the extrahepatic bile duct artery might be derived from the cystic artery, common hepatic artery, gastroduodenal artery, posterior portal vein artery, and arteria pancreaticoduodenal superior posterior. [ 15 16 17 18 ] For the blood distribution to extrahepatic bile ducts, Gunji et al . [ 19 ] and Cho et al .…”
Section: Discussionmentioning
confidence: 99%
“…I n the general population, anatomic variation of hepatic arteries ranges from 20 to 50% in different series 4,11,13,23 . Since the original paper done by Michels 20 , several studies have followed him and developed classification systems for the anatomic variants of hepatic arteries 1,10,12,13,17 . As a consequence, screening for these variations and a search for vascular reconstruction techniques to optimize the irrigation of the biliary tree and liver graft have taken place 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, increased knowledge on threedimensional anatomical position of these vessels and technological progress in vascular reconstruction have led to the development of techniques aiming to reestablish liver blood supply 9,18,21,27 . Furthermore, interventional radiological studies have shown that vessel position is very important to the rheological behavior of several anatomical variants and to the reconstructions ABCDDV/903 performed 10 . Thus, quality of reconstruction is essential to prevent arterial thrombosis that ultimately leads to graft loss.…”
Section: Introductionmentioning
confidence: 99%